Tools for the co-designing of housing transformations: A study on interaction and visualization modes - Eloy, S.; Raposo, M.; Costa, F.; Vermaas, P. E. (Formal Methods in Architecture. Advances in Science, Technology & Innovation, 2021)
In this paper we present and assess tools for visualizing architectonic modifications of existing housing in co-design projects with inhabitants. These tools should enable inhabitants to explore and understand design variations of alterations of their houses. This contribution is part of ongoing research on the use of artificial realities for supporting the transformations of existing housing in architectonically responsible ways. Such transformations may be needed after the delivery of housing, say after five years or later, due to changed regulation, the need of updates or changed living conditions of inhabitants. For arriving at architectonically responsible transformations, we use shape grammar system for defining possible modifications of the housing. For empowering inhabitants to understand and explore these modifications to their housing, we develop a transformation grammar tool—MyChanges—to visualize the modifications by three visualization modes, from fully immersive to non-immersive. Interviews and tests with real inhabitants were performed, and preliminary conclusions show that a tool like the MyChanges would have a good acceptance among inhabitants.